A novel energy assessment of urban wastewater treatment plants. (1st May 2018) - Di Fraia, S.; Massarotti, N.; Vanoli, L.
Highlights: A method to assess energy performance of wastewater treatment plants is proposed. Energy performance indicators are coupled with pollution removal efficiencies. The method is applied to a large database of wastewater treatment plants. Some classes of energy performance are introduced. Abstract: Wastewater treatment is a high energy consuming process, and its energy demand is considerably increasing due to the introduction of more restrictive standards on the quality of water effluents, that require advanced technologies for pollutant removal. Energy audits are carried out in order to improve energy efficiency of wastewater treatment plants, by introducing some measures, such as adjustments of the treatment scheme, or optimization of existing operational units. At the same time, energy recovery from wastewater treatment and its by-products is being implemented in order to reduce economic costs and environmental impact of the process. In order to assess the benefits resulting from implementation of these interventions, procedures for evaluation of energy performance of wastewater treatment plants are being developed. In this work, a novel method is proposed for assessing energy performance of wastewater treatment plants by coupling simple energy performance indicators with specific pollution removal efficiencies. This procedure is applied to a large database of wastewater treatment plants, in order to define some classes of energy performance depending on removal efficiency. The method is also used to analyse some Italian plants, representative of different design and management conditions. As a result, only 8.2% of around 300 plants presents the highest class of performance, considering the energy consumption related to the organic matter removal.